2007
DOI: 10.1016/j.virol.2007.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Tissue tropism and neuroinvasion of West Nile virus do not differ for two mouse strains with different survival rates

Abstract: West Nile virus (WNV) is a mosquito-borne flavivirus that infects the central nervous system of humans and other animals. In this study, we found that C3H/HeN (C3H) mice exhibited a higher morbidity and mortality than C57BL/6 (B6) mice. We compared tissue tropism, viral replication and kinetics for C3H and B6 mice during acute viral infection. WNV was detected in multiple tissues, including novel sites such as the skin, duodenum and pancreas, but the tropism was identical for the two strains. Additionally, vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 40 publications
9
102
1
2
Order By: Relevance
“…Blood samples were centrifuged (5,000 ϫ g, 5 min), and serum was removed and stored at Ϫ80°C for later titration. Tissues were weighed and processed as previously described (3). Virus was quantified in sera and clarified tissue homogenates by plaque assay on Vero cell monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were centrifuged (5,000 ϫ g, 5 min), and serum was removed and stored at Ϫ80°C for later titration. Tissues were weighed and processed as previously described (3). Virus was quantified in sera and clarified tissue homogenates by plaque assay on Vero cell monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…C3H/HeN mice showed higher morbidity and mortality than that of C57BL/6 mice after infection with the recombinant virus derived from a 2000 New York isolate, although viral tropism, viral load, and kinetics did not differ substantially between these strains. 6 Our unpublished observations from 6-week-old C3H mice that received footpad inoculation of 1,000 plaque-forming units of a NY99-6922 strain-derived plaque isolate revealed that infected mice developed neuronal necrosis ( Fig. 1) with infiltration of reactive microglia, neuronophagia, and perivascular infiltration of macrophage/microglial cells and lymphocytes (Fig.…”
mentioning
confidence: 87%
“…and transcardially perfused with 60 ml of phosphate-buffered saline (PBS) plus 1% fetal bovine serum (FBS). Tissues were harvested and processed as previously described (6).…”
Section: Cellsmentioning
confidence: 99%